Top ten most cited papers published in IJABE according to Google scholar - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2013)
1. Overview of biomass pretreatment for cellulosic ethanol production Yi Zheng, Zhongli Pan, Ruihong Zhang Int J Agric & Biol Eng, 2009; 2(3) Cited times: 106 2. Current status of adoption of no-till farming in the world and some of its main benefits Rolf Derpsch, Theodor Friedrich, Amir Kassam, Li Hongwen Int J Agric & Biol Eng, 2010; 3(1) Cited times: 49 3. Effect of nitrogen and extraction method on algae lipid yield Ying Shen, Zhijian Pei, Wenqiao Yuan, Enrong Mao Int J Agric & Biol Eng, 2009; 2(1) Cited times: 25 4. Size matters: small distributed biomass energy production systems for economic viability Roger Ruan, Paul Chen, Richard Hemmingsen, Vance Morey, Doug Tiffany Int J Agric & Biol Eng, 2008; 1(1) Cited times: 12 5. Mathematical modeling of microwave- assisted convective heating and drying of grapes Gokhan Bingol, Zhongli Pan, John S.Robert, Y. Onur Devres, Murat O.Balaban Int J Agric & Biol Eng, 2008; 1(2) Cited times: 10 6. Nondestructive assessment of quality of Nanfeng mandarin fruit by a portable near infrared spectroscopy Sun Xudong, Zhang Hailiang, Liu Yande Int J Agric & Biol Eng, 2009; 2(1) Cited times: 10 7. Optimization of Japanese beech hydrolysis treated with batch hot-compressed water by response surface methodology L